Serum cholesterol level nomograms for Iranian population; suggestion for national cut-offs. - Mostafa Hosseini; Shervin Taslimi; Mahmoud Yousefifard; Fereshteh Asgari; Koorosh Etemad; Hamid Heidarian Miri; Ali Rafei; Jalil Koohpayehzadeh; Iman Navid; Mohammad Mehdi Gouya (Tehran University of Medical Sciences, 2013)
High cholesterol levels are associated with increased risk of coronary heart disease and stroke. Understanding the distribution of serum cholesterol levels in each country is valuable index for use in public health planning. This study aimed to construct nomograms of total cholesterol (TC) levels and establish the cut-points specific to Iranian population.Data on serum TC levels of 19,630 non-institutionalized individuals aged 25-64 years from third national survey on non-communicable diseases (SuRFNCD) in 2007 were used to construct cholesterol nomograms. We proposed cutoff values for borderline and high TC levels based on rounded 75th and 90th percentiles in three age groups (25-34, 35-44 and 45-64) respectively.Average yearly increase of TC for males up to the age of 45 and females up to 64 were 1.15 and 1.03 mg/dl, respectively. TC levels were higher in females. In males, cutoff values for "borderline and high" TC levels were 195 and 220 mg/dl in 25-34, 210 and 240 mg/d in 35-44 and 215 and 245 mg/dl in 45-64 years old individuals. In women, these values were 200 and 225 mg/dl in 25-34,215 and 240 mg/dl in 35-44 and 235 and 265 mg/dl in 45-64 years old individuals respectively.Since TC levels are different in two sexes and change with age, we proposed different cutoffs for sex and age group. We think these cutoffs could be used in national public health planning.